1989
DOI: 10.1007/bf00584641
|View full text |Cite
|
Sign up to set email alerts
|

Patch-clamp study of cultured human sweat duct cells: amiloride-blockable Na+ channel

Abstract: The reabsorptive duct of the eccrine sweat gland has a large transepithelial conductance consisting mainly of a high conductance to Cl- and a smaller, amiloride-blockable Na+ conductance (Bijman and Frömter 1986; Quinton 1986). Cells have been cultured from sweat ducts and their properties previously studied in Ussing chambers (Pedersen 1988) and with microelectrodes (Jones et al. 1988). We have now studied the ion channels present in excised, inside-out patches of human cultured sweat duct cells, and find a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…This generally accepted I-V relationship of amiloride-sensitive Na transport is in contrast to the observation in the present study and suggests that the electrogenic Na transport in sheep rumen, which is amiloride-insensitive (30) and modulated by apical divalent cations (24), is a distinct Na pathway. However, it should be mentioned that a voltage-sensitive (the open probability increases with depolarization) amiloride-blockable Na channel has been described in cultured human sweat duct cells (21) and in A6 cells (16). Recently, Marunaka et al (32) have reported an amiloride-sensitive Na-permeable nonselective cation channel in the apical membrane of fetal alveolar epithelium with an increased open probability when the apical membrane is depolarized.…”
Section: G613mentioning
confidence: 99%
“…This generally accepted I-V relationship of amiloride-sensitive Na transport is in contrast to the observation in the present study and suggests that the electrogenic Na transport in sheep rumen, which is amiloride-insensitive (30) and modulated by apical divalent cations (24), is a distinct Na pathway. However, it should be mentioned that a voltage-sensitive (the open probability increases with depolarization) amiloride-blockable Na channel has been described in cultured human sweat duct cells (21) and in A6 cells (16). Recently, Marunaka et al (32) have reported an amiloride-sensitive Na-permeable nonselective cation channel in the apical membrane of fetal alveolar epithelium with an increased open probability when the apical membrane is depolarized.…”
Section: G613mentioning
confidence: 99%
“…In the sweat gland, the proximal tubule or secretory coil secretes an isoosmotic fluid which is then presented to the water impermeable apical membrane of the distal, reabsorptive tubule or excretory duct (28). No evidence for an amiloride-sensitive conductance was obtained in cultured human sweat gland secretory cells (17), whereas there is evidence for such sodium conductance in excretory ducts (2,13). Patch clamp study of cultured human sweat gland excretory duct provided evidence for an amiloride-sensitive (1 raM) sodium channel that was, however, characterized by a relatively high single channel conductance (15 pS) and was moderately selective (PN,/PK about 4) (13).…”
Section: Cellular Expression Of ~ ~ ~/ Renac Correlates With the Electrogenic Sodium Transport In Aldosterone-responsive Epitheliamentioning
confidence: 99%
“…Amiloride, a potassium‐sparing diuretic, is used clinically for the management of renal failure, 1 hypertension 2 and congestive heart failure 3 and experimentally as a pharmacological agent 4–6 . Amiloride exerts its effects by blocking Na + channels with high affinity 7,8 and H + channels 9 . Its effects are also mediated bys inhibition of Na + ‐related transporters, such as the Na + –Ca 2+ exchanger, 10 the Na + –H + antiporter 11 and the T‐ or ‐type Ca 2+ channel 12,13 at higher concentrations.…”
Section: Introductionmentioning
confidence: 99%